2011
DOI: 10.1182/blood-2010-07-292722
|View full text |Cite
|
Sign up to set email alerts
|

Immune modulation by Fas ligand reverse signaling: lymphocyte proliferation is attenuated by the intracellular Fas ligand domain

Abstract: Fas ligand (FasL) not only induces apoptosis in Fas receptor-bearing target cells, it is also able to transmit signals into the FasL-expressing cell via its intracellular domain (ICD). IntroductionFas ligand (FasL, CD95L, CD178, TNSF6) is a 40-kDa glycosylated type II transmembrane protein that belongs to the tumor necrosis factor (TNF) family. Its extracellular portion harbors a C-terminal TNF homology domain that assembles as homotrimers and mediates interactions with receptors. Interestingly, the 77-amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Even T reg numbers were identical although these cells are susceptible to homeostatic control by CD95. 42 Although CD95L activation is known to be a possible modulator of T-cell expansion, 21,22 re-isolated allogeneic T cells from APG101-treated mice showed no changes in proliferation toward alloantigen or third-party antigens compared with T cells isolated from GVHD suffering mice. T-cell expansion in APG101-treated mice was further confirmed by efficient T-cell invasion of host tissues in vivo, which was reported to be impaired if CD95L-deficient T cells were used as allogeneic effector cells.…”
Section: Apg101 Prevents Gvhd But Preserves Gvt Effect 563mentioning
confidence: 98%
See 2 more Smart Citations
“…Even T reg numbers were identical although these cells are susceptible to homeostatic control by CD95. 42 Although CD95L activation is known to be a possible modulator of T-cell expansion, 21,22 re-isolated allogeneic T cells from APG101-treated mice showed no changes in proliferation toward alloantigen or third-party antigens compared with T cells isolated from GVHD suffering mice. T-cell expansion in APG101-treated mice was further confirmed by efficient T-cell invasion of host tissues in vivo, which was reported to be impaired if CD95L-deficient T cells were used as allogeneic effector cells.…”
Section: Apg101 Prevents Gvhd But Preserves Gvt Effect 563mentioning
confidence: 98%
“…Although CD95L is best known for its role in apoptosis induction, it may also serve a function in reverse signaling, thereby modulating the immune function of CD95L-expressing cells. 21,22 Therefore, we first tested the effect of APG101 on apoptosis inhibition and T-cell function in vitro. B6-derived spleen cells were treated with recombinant CD95L and enhancer in the presence of increasing concentrations of APG101.…”
Section: Apg101 Inhibits Apoptosis But Does Not Interfere With T-cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Kirkin et al (41) observed an 11-kDa FasL intracellular domain (ICD), which was generated via sequential proteolysis and subsequently translocates to the nucleus where it modulates gene transcription. Furthermore, the analysis of knockin mice lacking the FasL ICD revealed that plasma cell numbers, generation of GC B cells, and, consequently, production of Ag-specific Abs in response to immunization with T celldependent or T cell-independent Ag are negatively regulated by FasL ICD-dependent signals (42). Because of the lack of suitable reagents allowing the complete functional blockade of FasL, including retrograde signaling by FasL ICD in vivo, we have initiated mouse breedings to generate FasL-deficient mice with a B cellspecific JAB1 deletion to address the role of overexpressed FasL during B cell development.…”
Section: Discussionmentioning
confidence: 99%
“…SPPL2a cleaves the N-terminal fragment (NTF) of the invariant chain (Ii; CD74) and is essential for the normal development of B cells and myeloid dendritic cells (32)(33)(34). SPPL2a has also been shown to cleave Fas ligand (FasL) to generate an intracellular domain (ICD) that negatively regulates B and T cell activation and proliferation downstream of antigen receptor triggering (35). Both SPPL2a and SPPL2b can cleave tumor necrosis factor alpha (TNF-␣) to produce an ICD that elicits production of the proinflammatory cytokine interleukin 12 (IL-12) by bone marrow-derived dendritic bated at 65°C for 15 min in the presence of SDS loading buffer and were separated by SDS-PAGE on 10% gels.…”
mentioning
confidence: 99%